2018
DOI: 10.3389/fbuil.2018.00020
|View full text |Cite
|
Sign up to set email alerts
|

Full Aeroelastic Model Testing for Examining Wind-Induced Vibration of a 5,000 m Spanned Suspension Bridge

Abstract: This paper presents an experimental investigation on wind-induced vibrations of a suspension bridge with ultimate main span length, including flutter and buffeting. Since the upper limit of a suspension bridge's main span can reach more than 5,000 m based on strength and weight of steel main cables, a feasible prototype with a span arrangement of 2,000 + 5,000 + 2,000 m has been proposed. In order to improve flutter stability, a twin box girder has been designed with a 40 m slot in center and two 20 m wide dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Later on, with the strong need to capture the complex three-dimensional mutual interaction of the structural oscillation and the airflow around it, more sophisticated full aero-elastic wind tunnel models were applied. In the case of a number of large span bridges, these advanced tests were used [4][5][6][7]. Both the section and full aero-elastic models have their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, with the strong need to capture the complex three-dimensional mutual interaction of the structural oscillation and the airflow around it, more sophisticated full aero-elastic wind tunnel models were applied. In the case of a number of large span bridges, these advanced tests were used [4][5][6][7]. Both the section and full aero-elastic models have their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…A pressure integration cannot reckon surface friction in, which may affect the accuracy of drag but has limited influence on lift and moment. Meanwhile, the full aeroelastic testing (Ge et al, 2018) indicated the role of buffeting was highlighted along vertical and torsional directions while the stochastic buffeting accounted for less than 20% of total lateral response. The static lateral deformation is more important in super-long cases.…”
Section: Major Resultsmentioning
confidence: 99%
“…The outlines of twin decks are in the background of an ultimate-long suspension bridge. In Ge et al (2018), a full aeroelastic model testing was carried out with a total length of 2000+5000 + 2000 m (Figure 1(a)). For this super-long span, a widely slotted TBG provides better aerodynamic stability than a single girder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, the RMS responses are the direct results of turbulence intensities. In the cases of I = 10% and 11% where intensities are close, the integral sales have a 25% difference because of the spire locations in the wind tunnel (details in Ge et al, 2018). However, the dynamic responses keep close to each other.…”
Section: Full Aero-elastic Buffeting Testingmentioning
confidence: 99%